2019
DOI: 10.1016/j.bej.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

CHO cell cultures in shake flasks and bioreactors present different host cell protein profiles in the supernatant

Abstract: Abbreviations: CHO, Chinese hamster ovary; HCP, host cell protein; IVCC, integrated viable cell concentration; mAb, monoclonal antibody; QbD, Quality by design; TDS, temperature downshift; VCD, viable cell density; vvm, gas volume flow per unit of liquid volume per minute; Highlights 1. Comparison of flask and bioreactor cultures at 37 o C and 32 o C 2. All four conditions produced similar HCP concentration and mAb/HCP ratio 3. Bioreactor cultures had significantly higher number of HCP species than flasks 4. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…However, previously observed fold-change magnitudes were much greater than those observed here, probably due to the large difference in the aging time scales between the two studies in addition to the subcloning of the parental host after suspension adaptation. Another contributing factor may be the change in upstream process (i.e., fed-batch culture in bioreactor vs. batch culture in flask), which could have helped to stabilize HCP levels in this case, and has been previously determined to influence HCP levels (Goey et al, 2019;Gronemeyer et al, 2016;Park et al, 2017). We were also able to reliably measure more HCPs due to improved MS instrumentation and the use of SWATH-MS, yielding a population that more closely agrees with the putative size of the CHO supernatant proteome (Kumar et al, 2015).…”
Section: Swath-ms Has Been Previously Leveraged To Characterize Cho Cellmentioning
confidence: 96%
“…However, previously observed fold-change magnitudes were much greater than those observed here, probably due to the large difference in the aging time scales between the two studies in addition to the subcloning of the parental host after suspension adaptation. Another contributing factor may be the change in upstream process (i.e., fed-batch culture in bioreactor vs. batch culture in flask), which could have helped to stabilize HCP levels in this case, and has been previously determined to influence HCP levels (Goey et al, 2019;Gronemeyer et al, 2016;Park et al, 2017). We were also able to reliably measure more HCPs due to improved MS instrumentation and the use of SWATH-MS, yielding a population that more closely agrees with the putative size of the CHO supernatant proteome (Kumar et al, 2015).…”
Section: Swath-ms Has Been Previously Leveraged To Characterize Cho Cellmentioning
confidence: 96%
“…One of the major factors contributing to HCP co‐purification is nonspecific interactions with the CDR regions of mAbs, and even small amino acid differences near the CDRs can have a large impact on the HCPs present in the drug product (Levy, 2014). However, other mechanisms are more generic, such as interactions with the Fc region of mAbs, chromatography resin, and upstream parameters (Zhang et al (2016), Goey et al, 2019), Levy (2014). Some co‐purifying HCPs are common and have been identified by multiple groups, whereas other HCPs can be molecule or cell line specific (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We first tested the FASP method using 0.5 mL 10 kDa cutoff Amicon columns. FASP is a commonly used sample preparation method for bottom-up proteomics that provides consistent and reproducible results for a variety of samples, including bioreactor supernatants. We processed 20 μL of filtered supernatant from a fed batch culture in CD CHO medium supplemented with CHO CD EfficientFeed B and vitamin K. We identified 526 proteins and 2441 distinct peptides in the sample (1% Global FDR) (Figure A). However, we also observed the presence of an abundant polymer (curved dotted lines showing increasing molecular weight (MW) and retention time (RT), Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…To change strategy, we compared the FASP protocol to three different bottom-up proteomics sample preparation methods: organic solvent protein precipitation, S-Trap columns, ,,,,, and SP3 with paramagnetic beads (Figure and Supplementary Table S1). ,, The organic solvent used here was a 1:1 mixture of methanol and acetone. , All methods have been previously shown to eliminate detergents from diverse samples, ,, and organic solvent precipitation and FASP have been previously used to prepare bioreactor supernatant samples for LC-MS/MS proteomics. We found that all three methods could remove the polymer(s) from the samples and that SP3 and S-Trap were better than precipitation (Figure B–E).…”
Section: Resultsmentioning
confidence: 99%